2021
DOI: 10.1038/s41577-021-00633-9
|View full text |Cite
|
Sign up to set email alerts
|

The type I interferonopathies: 10 years on

Abstract: As brutally demonstrated by the COVID-19 pandemic, an effective immune system is essential for survival. Developed over evolutionary time, viral nucleic acid detection is a central pillar in the defensive armamentarium used to combat foreign microbial invasion. To ensure cellular homeostasis, such a strategy necessitates the efficient discrimination of pathogen-derived DNA and RNA from that of the host. In 2011, it was suggested that an upregulation of type I interferon signalling might serve as a defining fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
207
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(209 citation statements)
references
References 138 publications
(156 reference statements)
1
207
0
1
Order By: Relevance
“…The description of the novel type I interferonopathy SAVI [1,2,50] thus indicated that STING1 gain-of-function mutations led to a severe Mendelian inflammatory ILD. These findings suggest a potential role for STING homeostasis in ILD.…”
Section: Historical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The description of the novel type I interferonopathy SAVI [1,2,50] thus indicated that STING1 gain-of-function mutations led to a severe Mendelian inflammatory ILD. These findings suggest a potential role for STING homeostasis in ILD.…”
Section: Historical Descriptionmentioning
confidence: 99%
“…Type I interferonopathies are a sub-group of Mendelian autoinflammatory diseases characterized by an overactivation of the type I interferon (IFN) pathway [1]. Under normal circumstances, IFNs are potent antiviral cytokines produced by cells when they sense foreign nucleic acids [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interferon is a group of signal proteins synthesized and released by host cells in response to stress and infections. Interferon exists widely in human and other animal organisms with highly species specifictiy (Crow and Stetson, 2021). According to the types of corresponding receptors, interferon can be divided into three types: IFN-I, type II interferon (IFN-II), and type III interferon (IFN-III; Hervas-Stubbs et al, 2011;Stanifer et al, 2019).…”
Section: Rna Modifications In Regulating Ifn Signaling Pathwaymentioning
confidence: 99%
“…During acute immune responses, IFN-I activation is usually beneficial to the host by providing transcriptional changes that allow the orchestration of an efficient response. However, when this activation persists, it becomes detrimental and is associated with chronic diseases (Crow and Stetson, 2021).…”
Section: Sensing Of Nucleic Acids By Cellular Receptors Activates The...mentioning
confidence: 99%
“…This model has been validated by in vitro experiment, mouse models and clinical data. Indeed, higher levels of circulating IFN-I in mouse models and in patients with mutations in gene encoding DNases and RNAses were detected (Crow and Stetson, 2021). In addition to this, organelles and genome integrity also play a critical part in safeguard mechanisms.…”
Section: Cytosolic Accumulation Of Self-nucleic Acids Allows Activati...mentioning
confidence: 99%